Detection and Typing Strategies for Pathogenic Escherichia coli - Rivas, Lucia (Springer, 2015)
Escherichia coli is one of the predominant facultative anaerobes in the human gastrointestinal tract. Many strains of E. coli are harmless and even provide many health benefits to the host, including preventing colonization of the gut by harmful pathogens. However, there are small groups of E. coli that have evolved and devel oped pathogenic strategies that can cause a broad spectrum of disease, including severe diarrheal disease and serious sequelae, in the human host and are more com monly referred to as pathogenic E. coli (Nataro and Kaper 1998). These pathogenic, diarrhea-causing E. coli can be broadly classified into six recognized pathotypes for which pathogenicity in outbreaks or volunteer studies has been established: En terotoxigenic E. coli (ETEC), Shiga-toxin producing E. coli (STEC, also referred to as Verotoxigenic or Verocytotoxigenic E. coli (VTEC), which includes a subgroup known as Enterohemorrahagic E. coli (EHEC), Enteropathogenic E. coli (EPEC), Enteroaggregative E. coli (EAEC), Enteroinvasive E. coli (EIEC), and Diffusely Adherent E. coli (DAEC) (Table 1.1)...